ISOLASI DAN IDENTIFIKASI SENYAWA ANTIBAKTERI DARI DAUN PETAI CINA (Leucaena leucocephala (Lam.) De Wit.) - , ARI SARTINAH, S.Si, Prof. Dr. Subagus Wahyuono, M.Sc.,Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Plant is one of important natural resource for treatment and maintaining public health. One of the plant that has been used as traditional medicine is Leucaena leucocephala. The leaves of this plant is used as medicine such as treatment of wound and swollen. This study was aimed to isolate and identify of antibacterial compound present ini L. leucocephala (Lam.) de Wit. leaves. The dried powder leaves of L. leucocephala (Lam.) de Wit. (300 g) was extracted using Soxhlet method with washbenzene followed by methanol as solvent reagent. Both extracts were tested for antibacterial acvtivity by diffusion test and monitored by TLC. The active extract was fractionated by vacuum liquid chromatography using washbenzene and ethyl acetat increasing polarity as mobile phase. The active fraction was refractionated further by vacuum liquid chromatography. The active compound of the active fraction was isolated by preparative thin layer chromatography to give p1a, p2a, p3a. The active compound (p2a) was tested its purity by TLC using three different mobile phases. Identification of structure was conducted by using UV, IR spectrophotometer, GC-MS and 1H-NMR datas. The UV-Vis, IR, GC-MS and 1H-NMR spectrum indicated that active compound was suggested to be a lupeol. Minimum concentration of this isolate as antibacterial agent towards of S. aureus was 100 Î¼g, with zone inhibition 9,6 mm.